Assessing the performance and economic viability of solar home systems: A way forward towards clean energy exploration and consumption. (May 2023) - Sun, Bohan; Gao, Ke; Liu, Shuai; Wei, Qiaoqiao; Wang, Hui
Abstract: Energy is an essential source of global economic expansion since it is related to fundamental generation and usage. In this context, solar home systems (SHS) are advantageous in two dimensions: reducing energy expenses and satisfying energy requirements. This research intends to assess the effectiveness of implementing SHS in the economic performance of China's small and medium-sized enterprises. Moreover, we investigate the moderating impact of knowledge of SHS between the elements of a deployment of SHS and the economic performance of small and medium-sized enterprises. The data was collected from 520 respondents, and the structural equation modeling (SEM) method was employed for data analysis. The findings showed that cost-efficient energy from SHSs has a continuous and considerable relationship with the economic performance of small and medium enterprises. Likewise, knowledge of SHS moderates significantly the links between efficient energy supply via SHS, the durability of SHS, and the economic performance of small and medium-sized enterprises. Further improvement of the economic performance of small and medium-sized enterprises is required by a greater emphasis on SHS, as shown by these results, which serve as good guidance for those who design regulations. Highlights: Investigated the performance of adopting solar home system. Also examined the moderating role of knowledge of solar home system. Data is analyzed using structural equation modeling. Cost-efficient energy significantly related with small and medium enterprises. Knowledge of solar home system moderate these relationships.